Optimisation of Cu+ impregnation of MOF-74 to improve CO/N2 and CO/CO2 separations - Evans,A; Cummings,M; Decarolis,D; Gianolio,D; Shahid,S; Attfield,M; Law,G; Petit,C (RSC Advances: an international journal to further the chemical sciences, 2020)
Carbon monoxide (CO) purification from syngas impurities is a highly energy and cost intensive process. Adsorption separation using metal–organic frameworks (MOFs) is being explored as an alternative technology for CO/nitrogen (N2) and CO/carbon dioxide (CO2) separation. Currently, MOFs' uptake and selectivity levels do not justify displacement of the current commercially available technologies. Herein, we have impregnated a leading MOF candidate for CO purification, i.e. M-MOF-74 (M = Co or Ni), with Cu+ sites. Cu+ allows strong π-complexation from the 3d electrons with CO, potentially enhancing the separation performance. We have optimised the Cu loading procedure and confirmed the presence of the Cu+ sites using X-ray absorption fine structure analysis (XAFS). In situ XAFS and diffuse reflectance infrared Fourier Transform spectroscopy analyses have demonstrated Cu+–CO binding. The dynamic breakthrough measurements showed an improvement in CO/N2 and CO/CO2 separations upon Cu impregnation. This is because Cu sites do not block the MOF metal sites but rather increase the number of sites available for interactions with CO, and decrease the surface area/porosity available for adsorption of the lighter component.